Precursor B- cell lymphoblastic lymphoma/leukaemia masquerading as epidermal cyst of scalp - Basab Bagchi; Surabhi Raj; Bindey Kumar; Amit Kumar Sinha; Sachin Bharti (Elsevier, 2020)
B-Lymphoblastic lymphoma (B-LBL) is a relatively uncommon neoplasm when compared to T-LBL or B-ALL. Here we report a case of a 11yr male child who presented with a swelling in the fronto-parietal scalp, diagnosed clinically and on FNAC as epidermal cyst. The biopsy and HPE confirmed the diagnosis of B-LBL. After 7 months of initial presentation and even before treatment could be initiated the patient evolved into B-ALL. The patient responded to chemotherapy (BFM2002)' and local radiotherapy and debridement of swelling. B-LBL has common extranodal presentation and can lead to diagnostic dilemma.